ParÃ¢metros genÃ©ticos para longevidade em vacas da raÃ§a Holandesa - Elisa Junqueira Oliveira; Suelen CorrÃªa da Silva; Claudia Cristina Paro de Paz; AnnaÃza Braga Bignardi; Vera LÃºcia Cardoso; Lenira El Faro (Boletim de Indústria Animal, 2012)
O artigo nÃ£o apresenta resumo em portuguÃªs.